The Influence of Location, Service Quality, Product Diversity and Price Perceptions on Purchasing Decisions at Utama Paint Shop Semarang - Halawa, Yefri Yanto; Hartoto, Witjaksono Eko (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to empirically examine the effect of location, service quality, product variety, and price perceptions on purchasing decisions at Toko Cat Utama Semarang. The population of this research is all consumers who buy and use the products of Toko Cat Utama Semarang. The sample used in this study was 96 respondents using a purposive sampling technique Then, the data collection method was through questionnaires and data analysis using SPSS 26. The results of this study indicate that location (X1), service quality (X2), product variety (X3), and price perceptions (X4) have a positive and significant effect on purchasing decisions (Y). Based on the coefficient of determination of 0.775, which means that 77.5 percent of the purchasing decision variable can be explained by location variables (X1), service quality (X2), product variety (X3), and price perceptions (X4), while the remaining 22.5 percent is explained by other variables outside of this study.